Research on spur face gear by electrochemical machining based on the complex surface mesh. (January 2020) - Huang, Liang; Cao, Yan; Jia, Feng; Lei, Yan
Abstract: The tooth surface of the spur face gear is a kind of complex space curved surface, in order to solve the technical defects in traditional NC milling manufacturing. This paper utilizes the complex tooth surface grid planning principle to establish the cathode surface firstly; Secondly, the orthogonal test, linear regression analysis and weighted comprehensive scoring system is adopted to obtain the optimal processing parameters; And finally, the Lagrange interpolation method is used to realize the modification of the cathode surface. The verification test shows that this method compared with the traditional NC milling, reduces the cost by 70% and the cycle by 75%, can realizes the rapid high-precision batch manufacturing of complex structure products.